Does Retirement Affect Voluntary Work Provision? Evidence from England, Ireland and the U.S. - Peter Eibich; Angelo Lorenti; Irene Mosca (Institute of Labor Economics (IZA), 2020)
Voluntary work is an important contribution for many non-profit organizations, such as charities, political and religious organizations. Older individuals make up a sizable share of the volunteer workforce, and volunteering is often regarded as an example of "active ageing". In this study, we examine whether retirement has a causal effect on the frequency of voluntary work provision in three English-speaking countries - England, Ireland and the U.S. We draw on data from the ELSA, TILDA and HRS studies and employ a harmonised approach in the empirical analysis. We use eligibility ages for old age pensions in an instrumental variable estimation to address potential confounding. We find that retirement increases the frequency of voluntary work provision in all three countries, especially among men. This suggests that labour market policies aimed at increasing labour force participation at older ages might have unintended consequences for the size of the volunteer workforce.
Keywords: J22; J26; 330; voluntary work; instrumental variable; retirement